2016
DOI: 10.1177/0149206316657593
|View full text |Cite
|
Sign up to set email alerts
|

Guilty by Association: Product-Level Category Stigma and Audience Expectations in the U.S. Craft Beer Industry

Abstract: While researchers have been increasingly interested in the notion of category stigma, they have largely focused on stigmatized industry categories. Because products serve as a key interface between producers and consumers, we suggest that product categories should play a prominent role in the stigmatization process. Product category stigma occurs when a product category is seen as violating the expectations of its audience members. We argue that when an organization offers a product from a stigmatized category… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 69 publications
1
79
0
2
Order By: Relevance
“…Other researchers have explored consumer perceptions of "authenticity," and found that craft beer drinkers have negative perceptions of beer produced by big brewers [11] (or even breweries that offer beer styles associated with big brewers [12]). There has been little research, however, on how these opaque patterns of ownership are reflected in "craft" beer selections at retailers.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers have explored consumer perceptions of "authenticity," and found that craft beer drinkers have negative perceptions of beer produced by big brewers [11] (or even breweries that offer beer styles associated with big brewers [12]). There has been little research, however, on how these opaque patterns of ownership are reflected in "craft" beer selections at retailers.…”
Section: Introductionmentioning
confidence: 99%
“…However, research finds that there are “perils” in explicitly claiming authentic organizational identities, suggesting that authenticity work is critical to product value in the new market, yet must be subtle and nuanced (Kovács et al., “Perils”). For instance, research integrating authenticity perspectives has explored the craft beer industry and organizational identities in contrast to mass‐production breweries, revealing how oppositional identities can increase product appeal and prevent organizational stigmatization (Barlow et al.; Verhaal et al.). These studies reveal a corresponding point of interest and a need for research from a cultural lens.…”
Section: Craft Brewing In the United Statesmentioning
confidence: 99%
“…In terms of production volumes, all craft breweries in this study can be categorised as small in size, and the large majority as microbreweries. Small craft breweries produce less than six million barrels yearly (Brewers Association, 2016), and microbreweries less than 15,000 barrels yearly (Barlow, Verhaal, and Hoskins, 2016).…”
Section: Methodsmentioning
confidence: 99%